Neoliberalism and the concept of governance: Renewing with an older liberal tradition to legitimate the power of capital - Andrew IVES (Cahiers du MIMMOC)
Neoliberalism, which has become the dominant current in political economy in western liberal democracies, presents itself in opposition to the reformist liberalism of the post-war consensus. The two streams of liberalism are both founded in methodological individualism, but neoliberalism breaks away from its counterpart through its commitment to limited government and through its belief in the inherent value of self-regulating markets. This does not represent an innovation, but instead should be seen as a return to an older liberal tradition. This paper will argue that the concept of governance as defined and put into practice by contemporary western governments meshes perfectly with the key tenets of neoliberalism. By advocating a method of management based on placing a variety of actors in competition, not only does it produce a model reminiscent of the free market, but it also contributes to the neoliberal objective of placing power squarely in the hands of those with capital.